Das Flugblatt im Medienverbund der Frühen Neuzeit: Bildtragendes Mediengut und Recycling-Produkt - Bellingradt, Daniel (Daphnis - Zeitschrift für Mittlere Deutsche Literatur und Kultur der Frühen Neuzeit, 2020)
One characteristic feature of the early modern media ensemble were the so-called 'small' and 'occasional' prints - a variety of pamphlet publications and single-sheet items that may be referred to as Flugpublizistik. In this article, one distinctive single-sheet variation, namely the early modern broadside with image and text parts, will be highlighted both as image transporting media and as a recycling product of the media ensemble. As is demonstrated using approaches from communication history and media economics, the early modern broadside with image and text parts is just another product of the most typical and constant processing of observed media-flows into new streams of media.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Broadsides; Early modern period; Flugblatt; Flugpublizistik; Media history; Media recycling